In vitro Antibacterial, Cytotoxic and Antioxidant Activities of Thai Traditional Medicine Called Trikatuk Remedy for Oral Cancer - Pattanacharoenchai, Napaporn; Yamprasert, Rodsarin (Trends in Sciences, 2026)
Oral cancer is commonly observed in patients with head and neck cancers. Efforts to identify novel antibacterial, cytotoxic and antioxidant agents that can prevent these diseases are ongoing. The ‘Trikatuk’ remedy, composed of 3 herbs-pepper (Piper nigrum Linn), long pepper (Piper retrofractum), and ginger (Zingiber officinale Roscoe) was recorded in Thai scripture as a remedy for diseases of the mouth and throat. Therefore, the present study investigated its antibacterial activity via the disc diffusion method, cytotoxic activity via the sulforhodamine B assay, and antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation decolourisation, and ferric ion reducing antioxidant power (FRAP) assays. The phytochemical composition of the extracts was analyzed using high-performance liquid chromatography (HPLC). The results showed that the 95% ethanolic extract from Trikatuk remedy did not inhibit the growth of Aggregatibacter actinomycetemcomitans, Staphylococcus aureus, and Streptococcus mutans. In contrast, the Trikatuk remedy showed high cytotoxic activity and very strong antioxidant activity with IC50 values of 30.68 and 25.21 µg/mL, respectively. Piperine, 6-gingerol and 6-shogaol were the major compounds in the ethanolic extract of Trikatuk remedy, found 223.43, 11.85 and 7.67 mg/g of extract, respectively. In conclusion, the data presented in this study revealed its cytotoxic and antioxidant properties, which correspond to the traditional Thai theory of using herbal recipes to treat various diseases. HIGHLIGHTS Trikatuk remedy exhibits significant cytotoxic and antioxidant activity. Trikatuk remedy can inhibit bacteria of common oral pathogens with high concentrations of extract. Piperine, 6-gingerol, and 6-shogaol are the major components of Trikatuk remedy. Findings validate traditional Thai applications of Trikatuk. GRAPHICAL ABSTRACT